The dark side of ISO 14001: The symbolic environmental behavior - Vera Ferrón Vílchez (European Research on Management and Business Economics (ERMBE), 2017)
Some of the academic research on ISO 14001 has focused on analyzing the benefits of its adoption. However, this international standard has also received some criticism, particularly in respect of the adoption of ISO 14001 when not accompanied by significant improvements in environmental performance. This study analyzes the relationship between the symbolic environmental behavior and the adoption of ISO 14001. In so doing, it uses binary logistic regression to analyze an international sample of 1961 manufacturing facilities that each employs more than 50 people. The results indicate that the higher the symbolic environmental performance of the firm, the greater the probability of adopting ISO 14001.
Keywords: Q53; Q56; M19; M14; 650; Symbolic environmental behavior; ISO 14001; Environmental performance; Logistic binary regression